Memahami Macam-Macam Zakat dan Wakaf dalam Manajemen Filantropi - Meli Amelia; Vina Rakhmawati; Icha Asaroh; Riyanti Wahyuni; Mohammad Ridwan (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Zakat and waqf are two essential instruments in Islamic teachings that hold great potential in supporting philanthropic activities and social development. This study aims to understand the various types of zakat an d waqf and how their management can be effectively integrated into modern philanthropic practices. Using a qualitative approach with literature review methods, this research explores the concepts, types, and management practices of zakat and waqf in socio-religious and economic contexts. The findings indicate that zakat includes several types such as zakat fitrah, zakat mal, and professional zakat, while waqf comprises productive waqf, cash waqf, and fixed asset waqf. In philanthropic management, both instruments require professional, transparent, and accountable governance to maximize their social impact. The integration of zakat and waqf into modern philanthropic systems not only strengthens the role of religious institutions but also contributes to poverty alleviation and sustainable development.